Whither Latin American Capital Markets? - de la Torre, Augusto; Schmukler, Sergio L. (World Bank, Washington, DC, 2012)
"Whither Latin American Capital Markets?" a study published by the Latin America and Caribbean Region of the World Bank in June 2004, analyzes the status and prospects for capital market development in Latin America. It reviews the evolution of securities markets in the region and related reforms and the factors driving their development. Importantly, the study analyzes not just domestic market activity, but also global capital markets trends, the participation of developing countries in those markets, and interactions and feedback loops between local and international markets.